INVESTIGATION OF EMERGENCY REMOTE EDUCATION EXPERIENCES OF PROSPECTIVE TEACHERS: A FRAMEWORK FOR PARTICIPATION - Eroğlu, Mehmet (ISMAIL HAKKI MIRICI, 2022)
The purpose of the study is to investigate prospective teachers' emergency remote education (ERE) experiences. The study was designed in a phenomenological pattern, one of the qualitative research methods. The study participants consisted of 125 prospective teachers in the education faculty of a state university in Turkey. The data was collected digitally with the interview form created by the researcher. Descriptive analysis was used in the analysis of the data. The results of the study showed that prospective teachers find ERE ineffective. Prospective teachers attend the field courses the most and the general culture courses the least. While the most critical factors that increase students' participation in the courses are the effectiveness of the course, its necessity, and difficulty, the most important factors that decrease their participation are ineffectiveness, unnecessary and easy courses. It has been determined that prospective teachers' participation in courses tends to decrease over time and the most important reason for this is the ineffectiveness of the courses. The achievement motivation of prospective teachers, adaptation, and the effectiveness of the course are factors that increase participation. It has been determined that prospective teachers' attitudes towards ERE tend to be negative over time, and the main reason for this is the ineffectiveness of the courses. The effectiveness of the course and the experience of ERE is the source of the positive attitudes of the prospective teachers toward ERE. Prospective teachers consider easy accessibility, effective use of time, flexibility, and increasing the use of technology as the most important advantages of ERE. Prospective teachers consider factors such as the ineffectiveness of courses, being unsuitable for practice courses, and being away from school life as the most important disadvantage of ERE. Prospective teachers think that they will experience professional inadequacy due to the ineffectiveness of the ERE process. However, they also stated that their experience in ERE is an important professional advantage. Prospective teachers suggested increasing the number of online courses, improving the infrastructure, and increasing the instructor's competencies for developing ERE. Considering the results obtained, a framework has been proposed for participation in distance education. © 2014 by International Online Journal of Education and Teaching (IOJET).
Keywords: Covid 19 pandemic; distance education; Emergency remote education; undergraduate teacher education